2023
DOI: 10.1111/apce.12412
|View full text |Cite
|
Sign up to set email alerts
|

Productivity drivers of infrastructure companies: Network industries utilizing economies of scale in the digital era

Abstract: What drives the productivity dynamics of infrastructure companies? Using a panel of firms in 14 countries, we study total factor productivity (TFP) enhancers of utility and network services companies. We find that moving TFP closer to the technological frontier drives productivity growth at higher speeds in Asian countries than in European countries. We also find that financial leverage exerts a positive effect on TFP growth for larger infrastructure firms and that more financially developed countries utilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…They contend that despite the anticipated benefits in terms of efficiency savings and revenue generation associated with investments in IT and IS, the implementation of technology has not resulted in enhanced OP, as posited by the productivity paradox theory. Nakatani (2023) agrees with the notion that the relationship between investments in AI technologies and productivity may be more intricate than previously assumed. According to Bjerke-Busch and Thorp (2022), the successful implementation of AI technologies is more likely when accompanied by modifications in managerial and organizational practices.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They contend that despite the anticipated benefits in terms of efficiency savings and revenue generation associated with investments in IT and IS, the implementation of technology has not resulted in enhanced OP, as posited by the productivity paradox theory. Nakatani (2023) agrees with the notion that the relationship between investments in AI technologies and productivity may be more intricate than previously assumed. According to Bjerke-Busch and Thorp (2022), the successful implementation of AI technologies is more likely when accompanied by modifications in managerial and organizational practices.…”
Section: Discussionsupporting
confidence: 90%
“…According to Mikalef and Gupta (2021), the development of AIC has the potential to enhance OP in government organizations. The productivity paradox theory elucidates various concerns regarding the association between technology and productivity (Nakatani, 2023). The decline in productivity, despite the growing investments in advanced technologies such as AI, can be attributed to methods and evaluation challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The positive coefficient of firm size indicates economies of scale in the food industry. The magnitude of scale economies (i.e., the size of estimated coefficients of firm size) in the food sector is found to be slightly smaller than that in the infrastructure sector studied by Nakatani (2023a). We also examined a different definition of firm size for a further robustness check by using a lagged natural logarithm of sales in Table A5 in the appendix.…”
Section: Nakatani | 195mentioning
confidence: 95%
“…Aghion et al (2019) andNakatani (2023a) found the nonlinear effect of leverage on TFP growth, which is analogous to the inverted U-shaped relationship between public debt and fiscal performance because net benefits to debt financing arise for firms or countries with low debt levels for better resource allocation but decrease as leverage reaches high levels, inducing moral hazard(Nakatani 2021b). …”
mentioning
confidence: 94%
“…This econometric specification is an extension of the empirical strategy developed byNakatani (2021Nakatani ( , 2023a, whose dependent variable was the differenced natural logarithm of TFP, approximating TFP growth Nakatani (2023b). studies the same topic, using cross-country firm-level data.…”
mentioning
confidence: 99%